Atopic Dermatitis - Williams, Hywel C. (Massachusetts Medical Society, 2005)
A 10-year-old girl with atopic dermatitis reports itching that has recently become relentless, resulting in sleep loss. Her mother has been reluctant to treat the girl with topical corticosteroids, because she was told that they damage the skin, but she is exhausted and wants relief for her child. How should the problem be managed?